Implementasi Fatwa DSN MUI No. 75/DSN-MUI/VII/2009 Terhadap Bisnis MLM Syariah (Studi di PT. Best Serang) - Seyella Amanda Luthfia; Dedi Sunardi; Nita Anggraeni (MUAMALATUNA, 2022)
Microsoft Office Translator Microsoft Office Translator English translation. Multilevel Marketing is also called network marketing because there are more and more members and form a network. The presence in the modern era world makes business opportunities for people who want to change their finances for the better and be free from debt by that reason this opportunity is one of the goals that are in demand by people who want to be quickly free from debt problems. PT. Bandung Eco Sinergy is a PLBS (Sharia Tiered Direct Sales) company or multilevel marketing. This company not only focuses on selling products but by expanding the network will also get benefits, besides that the products sold are relatively expensive compared to similar products and the rewards given are worth billions and make it attractive for people to join the business in this company. The company also claims to be in accordance with sharia and has received certification from DSN-MUI.